Faktor yang Berpengaruh pada Perilaku Seksual Remaja di Perkotaan dan Pedesaan - Suarni, Lisa; Fitarina, Fitarina; Aliyanto, Warjidin (Jurnal Kesehatan, 2020)
The effect of free sex on reproductive health is very real, namely the transmission of sexually transmitted infections (STIs) with all its consequences, a pregnancy outside of marriage and consequently an increase in the incidence of abortion, the psychological pressure to depression. It can be seen that the increasing incidence of STIs, abortion, and depression rates in society is increasing. The research objective was to determine the factors related to Adolescent Sexual Behavior in North Lampung. This study used an explanatory research design with a cross-sectional approach. A sample of 500 people, with a proportion of 250 samples from urban and 250 rural adolescents. The variables related to adolescent sexual behavior in rural areas were the variable of religiosity with a p-value of 0,00, knowledge with a p-value of 0,00, sexual attitudes with a p-value of 0,00, sexual activity with a p-value of 0.06, social support. with a p-value of 0,00 and in urban areas the related variables were self-esteem with a p-value of 0,10, religiosity with a p-value of 0,00, social activity with a p-value of 0,12, health service attitudes with a p-value 0,00, sexual attitude with a p-value of 0,00, sexual activity with a p-value of 0,00, self-confidence with a p-value of 0,24. Multivariate analysis found that the most dominant factor associated with sexual behavior is sexual attitudes with an OR=28,748. Religiosity, sexual activity, sexual attitudes affect sexual behavior in rural and urban areas. Sexual attitudes are the most dominant factor affecting adolescent sexual behavior in rural and urban areas.